Implementing the sustainable development goals in Nigeria : barriers, prospects, and strategies - Ekhator, Eghosa O.; Miller, Servel; Igbinosa, Etinosa (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book explores Nigeria's progress towards achieving the Sustainable Development Goals, presenting key country-specific lessons, as well as providing innovative solutions and practices which are transferrable to other emerging economies. Despite all of Nigeria's potential, and substantial oil revenues, poverty remains widespread and the country faces many challenges. The contributors to this book provide comparative historical and contemporary analysis of the main challenges for achieving progress in the SDGs, and make recommendations for the most effectives ways of developing, adopting, disseminating and scaling them. Starting with the conceptualisation and evolution of the SDGs, the book goes on to consider the goal on ending poverty, and the urgent need to combat climate change and its impacts. The book also reflects on the role of business and taxation, and the cultural and societal dimensions of the SDGs, including education, gender, and the role of the church. Overall, the book focuses on knowledge/implementation gaps and the role of collaborative partnerships and disruptive technologies in implementing the framework in general. This book will be of interest to scholars, policy makers and practitioners of sustainable development and African studies, as well as those with a particular interest in Nigeria"--
Introduction: Evolution of the SDGs Framework / Eghosa Ekhator, Servel Miller and Etinosa Igbinosa -- The Legal Framework for the implementation of the Sustainable Development Goals in Nigeria / Nathaniel Inegbedion and Godwin Umoru -- Food Security through Technological Innovations in Agriculture: What Role for Law in Nigeria? / Juliet Amienrovbiye and Odunagbon Theodora Osagie -- Implementing the Teaching Manpower Policy in Nigeria: An Imperative for Sustainable Development / Philip Igenegbai and Michael Osakpamwan Osasuyi -- The Environment, Climate Change and Underdevelopment of Nigerian Cities / Ibukun Ajayi, Eguonor Oleabhiele and Eseosa Enobakhare -- Towards Successful Delivery of Clean Drinking Water by 2030 in Nigeria: Dealing with the Challenges of Climate Change and Poor Environmental Practices / Vincent N. Chigor, Chidiebele E.I. Nwankwo, Chinyere B. Chigor et al. -- Examining Global Court Practices in Reducing Climate Change Impacts through Litigation: Lessons for Nigeria / Edward Okumagba -- Towards Corporate Sustainability in Nigerian Corporations: Opportunities and Disruptions / Oludara Akanmidu and Simisola Akintoye -- Taxation and the Implementation of Sustainable Development Goals in Nigeria / Emo Idornigie Pearce and Chisa Onyejekwe -- SDGs and Private Public Partnerships in Nigeria / Newman U. Richards -- SDG 3 and Maternal Health Rights: A Biosocial Approach to ending the VVF Scourge in Northern Nigeria / Hadiza Hamma -- Churches and the Achievement of the Sustainable Development Goals in Nigeria / Omole Iyayi and Pedi Obani -- Staff Awareness of the Role of Education in Sustainable Development Goals: Evidence from the University of Benin / Omoyebagbe Rosaline Dania and Esther Obiageli Okobia -- Towards an Inclusive Implementation of Sustainable Oceans, Seas and Marine Resources -SDG14: A Holistic Approach in Nigeria / Ifesinachi Okafor-Yarwood and Clement Sefa-Nyarko.
Keywords: Sustainable Development Goals; Sustainable development -- Nigeria; BUSINESS & ECONOMICS / Development / Sustainable Development